Potential and Trends of IoT Application in Agriculture in Vietnam - Doan Minh Quan; Hải Vân Trần Thị (Syntax Corporation Indonesia, 2023)
Vietnam is a country with a lot of potential and strengths in agriculture, but in the current period, along with the narrowing of arable land, the quality of soil and the increasingly harsh climate have caused difficulties for activities. Along with the strong development of the industrial revolution 4.0, the application of Internet of Things (IoT) technology in agriculture is increasingly popular. However, for the application to be synchronized and to effectively exploit IoT technology resources in the agricultural sector, it is necessary to have a policy orientation on science and application from the government. This article will address the outstanding issues of IoT application in Vietnamese agriculture and point out some potential applications.